Investigation of the relationship between executive functions and social cognition in hearing-impaired children: A cross-sectional study - Awed, Huda Shaaban; Alotaibi, Nouf Nawar (Edelweiss Applied Science and Technology, 2025)
The current study aimed to explore the relationship between executive functions and social cognition in hearing-impaired children. The sample comprised 162 students (89 males, 73 females) with hearing impairments enrolled in integration programs in the cities of Najran, Abha, and Jazan in southern Saudi Arabia, with an average age of 12.9 years (standard deviation = 1.92 years). A descriptive analytical approach was employed, utilizing the Barkley Executive Function Deficit Scale for Children and Adolescents (BDEFS-CA) and the Social Cognitive Scale. The findings revealed a statistically significant correlation between executive functions and social cognition. Additionally, no significant differences were found between males and females regarding their executive functions and social cognition. Notably, social cognition accounted for 77% of the variance in executive function scores. This preliminary study offers valuable insights into potential strategies and programs for training executive function tasks, which can significantly influence various aspects of social and cognitive development in hearing-impaired children.